Appropriateness of antibiotic management of uncomplicated skin and soft tissue infections in hospitalized adult patients. Issue 1 (December 2016) - Walsh, Thomas; Chan, Lynn; Konopka, Chelsea; Burkitt, Michael; Moffa, Matthew; Bremmer, Derek; Murillo, Monika; Watson, Courtney; Chan-Tompkins, Noreen
Abstract Background Skin and soft tissue infections (SSTIs) are a leading cause for hospitalizations in the United States. Few studies have addressed the appropriateness of antibiotic therapy in the management of SSTIs without complicating factors. We aimed to determine the appropriateness of antibiotic treatment duration for hospitalized adult patients with uncomplicated SSTIs. Methods This was a retrospective analysis performed at two academic medical centers in Pittsburgh, Pennsylvania on patients aged 18 years and older with primary ICD-9 code for SSTIs admitted August 1st, 2014–March 31st, 2015. The primary outcome was the appropriateness of antibiotic treatment duration for uncomplicated SSTIs. Secondary objectives included the appropriateness of antibiotic agent spectrum, duration of inpatient length of stay (LOS), utilization of blood cultures and advanced imaging modalities, and re-hospitalization for SSTI within 30 days of discharge from the index admission. Results A total of 163 episodes were included in the cohort. The mean duration of total antibiotic therapy was 12.6 days. Appropriate duration was defined as receipt of total antibiotic duration of less than 10 days and occurred in 20.2% of patients. Twenty eight percent of patients received antibiotics for greater than 14 days. Seventy three (44.8%) patients received greater than 24 h of inappropriate extended spectrum gram-negative coverage; 65 (39.9%) received anaerobic coverage. Conclusions In the majority of patients, treatment duration was excessive. Inappropriate broad spectrum antibiotic selection was utilized with regularity for SSTIs without complicating factors. The management of uncomplicated SSTIs represents a significant opportunity for antimicrobial stewardship.